Incremental value of quantitative CMR including parametric mapping for the diagnosis of acute myocarditis. (17th October 2015) - Luetkens, Julian A.; Homsi, Rami; Sprinkart, Alois M.; Doerner, Jonas; Dabir, Darius; Kuetting, Daniel L.; Block, Wolfgang; Andrié, René; Stehning, Christian; Fimmers, Rolf; Gieseke, Juergen; Thomas, Daniel K.; et al.
Abstract: Aim: Cardiac magnetic resonance (CMR) can visualize inflammatory tissue changes in acute myocarditis. Several quantitative image-derived parameters have been described to enhance the diagnostic value of CMR, but no direct comparison of these techniques is available. Methods and results: A total of 34 patients with suspected acute myocarditis and 50 control subjects underwent CMR. CMR protocol included quantitative assessment of T1 relaxation times using modified Look-Locker inversion recovery (MOLLI) and shortened MOLLI (ShMOLLI) acquisition schemes, extracellular volume fraction (ECV), T2 relaxation times, and longitudinal strain. Established Lake-Louise criteria (LLC) consisting of T2-weighted signal intensity ratio (T2-ratio), early gadolinium enhancement ratio (EGEr), and late gadolinium enhancement (LGE) were assessed. Receiver operating characteristics analysis was performed to compare diagnostic performance. Areas under the curve of native T1 (MOLLI: 0.95; ShMOLLI: 0.92) and T2 relaxation times (0.92) were higher compared with those of the other CMR parameters (T2-ratio: 0.71, EGEr: 0.71, LGE: 0.87, LLC: 0.90, ECV MOLLI: 0.77, ECV ShMOLLI: 0.80, longitudinal strain: 0.83). Combined with LGE, each native mapping technique outperformed the diagnostic performance of LLC ( P < 0.01, respectively). A combination of native parameters (T1, T2, and longitudinal strain) significantly increased the diagnostic performance of CMR compared with LLC without need of contrast media application (0.99 vs. 0.90; P = 0.008). Conclusion: In patients suspected of having acute myocarditis, diagnostic performance of CMR can be improved by implementation of quantitative CMR parameters. Especially, native mapping techniques have the potential to replace current LLC. ClinicalTrials.gov number: NCT02299856.